Molecular imaging nanoprobes for theranostic applications - He, Haozhe; Zhang, Xindan; Du, Lihua; Ye, Minwen; Lu, Yonglai; Xue, Jiajia; Wu, Jun; Shuai, Xintao (Advanced drug delivery reviews, 2022)
[Display omitted] As a non-invasive imaging monitoring method, molecular imaging can provide the location and expression level of disease signature biomolecules in vivo, leading to early diagnosis of relevant diseases, improved treatment strategies, and accurate assessment of treating efficacy. In recent years, a variety of nanosized imaging probes have been developed and intensively investigated in fundamental/translational research and clinical practice. Meanwhile, as an interdisciplinary discipline, this field combines many subjects of chemistry, medicine, biology, radiology, and material science, etc. The successful molecular imaging not only requires advanced imaging equipment, but also the synthesis of efficient imaging probes. However, limited summary has been reported for recent advances of nanoprobes. In this paper, we summarized the recent progress of three common and main types of nanosized molecular imaging probes, including ultrasound (US) imaging nanoprobes, magnetic resonance imaging (MRI) nanoprobes, and computed tomography (CT) imaging nanoprobes. The applications of molecular imaging nanoprobes were discussed in details. Finally, we provided an outlook on the development of next generation molecular imaging nanoprobes.